Acid‐regulated gene expression of Helicobacter pylori: Insight into acid protection and gastric colonization. Issue 3 (25th April 2018) - Marcus, Elizabeth A.; Sachs, George; Scott, David R.
Abstract: Background: The pathogen Helicobacter pylori encounters many stressors as it transits to and infects the gastric epithelium. Gastric acidity is the predominate stressor encountered by the bacterium during initial infection and establishment of persistent infection. H. pylori initiates a rapid response to acid to maintain intracellular pH and proton motive force appropriate for a neutralophile. However, acid sensing by H. pylori may also serve as a transcriptional trigger to increase the levels of other pathogenic factors needed to subvert host defenses such as acid acclimation, antioxidants, flagellar synthesis and assembly, and CagA secretion. Materials and Methods: Helicobacter pylori were acid challenged at pH 3.0, 4.5, 6.0 vs nonacidic pH for 4 hours in the presence of urea, followed by RNA‐seq analysis and qPCR. Cytoplasmic pH was monitored under the same conditions. Results: About 250 genes were induced, and an equal number were repressed at acidic pHs. Genes encoding for antioxidant proteins, flagellar structural proteins, particularly class 2 genes, T4SS/Cag‐PAI, Fo F1 ‐ATPase, and proteins involved in acid acclimation were highly expressed at acidic pH. Cytoplasmic pH decreased from 7.8 at pHout of 8.0 to 6.0 at pHout of 3.0. Conclusions: These results suggest that increasing extracellular or intracellular acidity or both are detected by the bacterium and serve as a signal to initiate increased production of protective and pathogenic factors needed to counter host defenses for persistent infection. These changes are dependent on degree of acidity and time of acid exposure, triggering a coordinated response to the environment required for colonization.